Resveratrol promotes cholesterol efflux from dendritic cells and controls costimulation and T-cell activation in high-fat and lipopolysaccharide-driven atherosclerotic mice - Zhang, Linhui; Wang, Haixia; Wang, Zishan; Xu, Jianyi; Wang, Mengyuan; Wang, Wenxin; He, Qiongshan; Yu, Yun; Yuan, Dongping; Bu, Guirong; Qiu, Runze; Long, Jun (Frontiers in Cardiovascular Medicine, 2024)
Cholesterol aggregation in dendritic cells (DCs) triggers an inflammatory response and accelerates the development of atherosclerosis (AS). Resveratrol (RES), a natural compound with anti-inflammatory and cholesterol metabolism regulatory properties, has been shown to influence the maturation and inflammatory functions of DCs. However, its relationship with cholesterol metabolism remains unclear. This study aimed to explore the roles of RES in cholesterol metabolism and inflammatory behaviors of DCs in the context of AS. We analyzed the effect of RES on cholesterol efflux from ApoE−/− bone marrow-derived dendritic cells (BMDCs) using qRT-PCR, Western blot, and cholesterol efflux assays; identified the inflammatory status of RES-treated BMDCs and co-cultured T cells using flow cytometry and ELISA; confirmed the effect of RES on blood lipids, atherosclerotic lesions, cholesterol metabolism, and inflammatory response in high-fat diet and lipopolysaccharide-treated ApoE−/− mice; and explored the potential targets of RES in regulating inflammatory behavior via molecular docking. The results revealed that RES promotes cholesterol efflux, increases the expression of efflux transporter ABCA1, and decreases liver X receptor alpha (LXRα) expression in response to a decrease in intracellular cholesterol in ApoE−/− BMDCs. RES also reduced MHC-II+ cells and downregulated costimulatory molecule CD80 in BMDCs with decreased IL-6 and increased IL-2 production, and suppressed T-cell activation and modulates IL-22 and IL-10 secretion via BMDCs. Furthermore, we confirmed that RES relieves arterial lesions and regulates blood lipids in ApoE−/− mice. RES demonstrated ABCA1 upregulation and LXRα downregulation effects in the aorta and regulated costimulation molecules and Th17/Treg cytokines in the spleen. Furthermore, RES showed multiple hydrogen bonding and low binding energy with ABCA1, suggesting that ABCA1 is a potential target of RES to modulate the inflammatory properties of BMDCs. Our study demonstrated that RES regulates cholesterol efflux and inflammatory behavior in BMDCs, contributing to the control of AS progression and offering new insights for managing inflammatory diseases.